Factors Influencing Economic Empowerment in Tourism Development - Rachmawati, Eva; Fountain, Joanna; Mackay, Michael (Economics and Finance in Indonesia, 2021)
Tourism is believed to be able to empower people economically, both at the individual and community levels, by providing various employment and business opportunities to community members to help alleviate poverty. This study offers insights into community empowerment outcome, particularly in economic dimension, through a quantitative approach. This study aims to identify the level of community empowerment outcome perceived by the local communities in tourism development in their area and analyze the factors that influence the outcome. Employing a mixed-methods approach, this study collected data through household survey, field and participatory observation, and document analysis. The questionnaire responses were analyzed using descriptive statistical analysis (i.e., frequency distribution and cross tabulation) and chi-square analysis. The findings suggest that tourism was able to increase the income of the people working in the tourism sector. However, only several people perceived that tourism could provide benefits for them. Several factors influencing the community perception related to economic empowerment in tourism development were identified. These include involvement in the tourism industry, community culture (kinship), nature of tourism affecting the type of available job, lack of engagement, lack of capital, education, and geographical factors.